2023
DOI: 10.1007/s13369-023-07623-0
|View full text |Cite
|
Sign up to set email alerts
|

Critical Analysis of the Use of Semiempirical Models on the Dehydration of Thin-Layer Foods Based on Two Study Cases

Abstract: Moisture transport during food drying can be phenomenologically described by Fick’s second law and by the so-called anomalous diffusion model. However, in the literature, many studies have shown the extensive use of empirical/semiempirical models (EMs/SEMs) to adjust experimental data for the drying of thin-layer foods. This research aims to perform a critical analysis of the most commonly used EMs/SEMs and compare them with Fick’s second law and an anomalous diffusion model using two different sets of hot-air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Several studies have concluded that the fit with the anomalous model is better than that with Fick’s model [ 31 , 54 , 62 , 93 ]. Vega-Castro et al [ 95 ] concluded that the reason is that the anomalous model has a sound phenomenological description of the process and a high capacity to adjust empirical data.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have concluded that the fit with the anomalous model is better than that with Fick’s model [ 31 , 54 , 62 , 93 ]. Vega-Castro et al [ 95 ] concluded that the reason is that the anomalous model has a sound phenomenological description of the process and a high capacity to adjust empirical data.…”
Section: Resultsmentioning
confidence: 99%
“…Several mathematical models were used to determine the kinetics of drying mango seeds (local and hybrid) and to calculate the ideal drying parameters to evaluate the performance of the drying process. These mathematical models can be divided into three major categories: theoretical, semitheoretical, and empirical 47 . The first category of models considers the internal resistance to moisture transfer only, whereas the other two consider the external resistance to moisture transfer between the seeds and air 48 .…”
Section: Methodsmentioning
confidence: 99%
“…The first category of models considers the internal resistance to moisture transfer only, whereas the other two consider the external resistance to moisture transfer between the seeds and air 48 . The models most commonly used for oilseeds and agricultural products are empirical and semitheoretical models, based on Fick's second law 47 . Different empirical and semiempirical mathematical models have different performance and fitness to experimental data, so it is essential to select a good mathematical drying model that best fits the drying curves under different conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations